A systematic mapping review of the evolution of the rat Forced Swim Test: protocols and outcome parameters - Brandwein, Christiane; Leenaars, Cathalijn H. C.; Becker, Laura; Pfeiffer, Natascha; Iorgu, Ana-Maria; Hahn, Melissa; Vairani, Gaia A.; Lewejohann, Lars; Bleich, André; Mallien, Anne Stephanie; Gass, Peter (Pharmacological research, 2023)
As depression is projected to become the leading mental disease burden globally by 2030, understanding the underlying pathology, as well as screening potential anti-depressants with a higher efficacy, faster onset of action, and/or fewer side-effects is essential. A commonly used test for screening novel antidepressants and studying depression-linked aspects in rodents is the Porsolt Forced Swim Test. The present systematic mappping review gives a comprehensive overview of the evolution and of the most prevalently used set-ups of this test in rats, including the choice of animals (strain, sex, and age), technical aspects of protocol and environment, as well as reported outcome measures. Additionally, we provide an accessible list of all existing publications, to support informed decision-making for procedural and technical aspects of the test, to thereby enhance reproducibility and comparability. This should further contribute to reducing the number of unnecessarily replicated experiments, and consequently, reduce the number of animals used in future.